Effect of Employee Engagement and Continuance Commitment on Employee Performance - Dedi Hadian (LPPM STMIK Mardira Indonesia, 2022)
This study aims to determine the effect of employee engagement and continuance commitment on employee performance. To find out the magnitude of the effect of employee engagement and continuance commitment on employee performance, the researchers used a survey approach to employees who work in two government agencies in Bandung. The number of respondents involved in the study were 71 employees. Researchers used path analysis to analyze research data. The results showed that employee engagement has a direct effect of 36.3%, the indirect effect through continuance commitment is 11.1%, so that the total effect is 47.4%. Continuance commitment has a direct effect of 13.5%, an indirect effect through its relationship with employee engagement of 11.1%, so that the total effect is 24.6%. And the total influence of employee engagement and continuance commitment on employee performance is 72% with other factors of 28%. The implications of the study indicate that the presence of employee engagement and continuance commitment will have an impact on increasing employee performance.